Roles of extracellular polymeric substances in enhanced biological phosphorus removal process - Li, Wen-Wei; Zhang, Hai-Ling; Sheng, Guo-Ping; Yu, Han-Qing (Water research (Oxford), 2015)
Enhanced biological phosphorus removal (EBPR) process is known to mainly rely on the ability of phosphorus-accumulating organisms to take up, transform and store excess amount of phosphorus (P) inside the cells. However, recent studies have revealed considerable accumulation of P also in the extracellular polymeric substances (EPS) of sludge, implying a non-negligible role of EPS in P removal by EBPR sludge. However, the contribution of EPS to P uptake and the forms of accumulated extracellular P vary substantially in different studies, and the underlying mechanism of P transformation and transportation in EPS remains poorly understood. This review provides a new recognition into the P removal process in EBPR system by incorporating the role of EPS. It overviews on the characteristics of P accumulation in EPS, explores the mechanism of P transformation and transportation in EBPR sludge and EPS, summarizes the main influential factors for the P-accumulation properties of EPS, and discusses the remaining knowledge gaps and needed future efforts that may lead to better understanding and use of such an EPS role for maximizing P recovery from wastewater. [Display omitted] •An updated overview on the characteristics of P accumulation in EPS is provided.•Mechanisms of P transformation and transportation in sludge and EPS are explored.•Main influential factors on the P-accumulation properties of EPS are analyzed.•Remaining knowledge gaps and needed future efforts are highlighted.